Patterns, aetiology and associated complications of maxillofacial fractures at a tertiary care centre: a cross-sectional observational study - Srivastava, Utkarsh; Haobijam, Nabakishor; Palin, Kh (International Surgery Journal, 2025)
Background: Maxillofacial fractures impose a major challenge in trauma care, affecting patient outcomes and healthcare resource utilisation. This study aimed to assess the patterns, aetiology and associated complications of maxillofacial fractures at a tertiary care centre. Methods: This cross-sectional observational study was carried out among patients who presented with trauma and had maxillofacial fractures at a tertiary care unit from May 2019 to April 2022. A thorough clinical examination and radiological investigation were carried out and after the diagnosis of maxillofacial fractures, a structured questionnaire was used to obtain relevant information regarding the patient's social-demographic status and aetiology. Clinical findings, treatment needs of the patients, as well as complications, were noted. The data was analysed using the Statistical Package for Social Sciences (SPSS) software version 20.0. Results: Overall, 155 patients were identified, where most of them were aged between 21 and 30 and a male predominance was noted in this study (87.7%). Road traffic accidents (RTAs) accounted for the most common cause (86.5%), followed by assault (7.1%) and falls (4.5%). Out of 155 patients, 71.6% suffered from midfacial fractures, followed by mandibular fractures (20.6%), panfacial fractures (5.1%) and the rest had both (2.5%). About 68.38% patients underwent Open reduction and internal fixation, 30% of patients underwent Intermaxillary fixation, closed reduction of their fractures (20.64%) and 9.03% patients underwent conservative management. Conclusions: Maxillofacial fractures are most common in young people aged 21 to 30, generally as a result of RTA and the majority of them have midfacial fractures, most of which are zygomaticomaxillary complexes.